Study of the Properties of Concrete Based on Non-Fired Alkaline Binders - Khamidov, A. I.; Khakimov, S. (Journal of Geography, Regional Planning and Development, 2024)
The article deals with the use of film-forming materials for the care of freshly laid concrete based on non-firing alkaline binders, the results of studies to determine the strength, frost resistance and plastic shrinkage of concrete are presented.